Moving Subjects, Stagnant Paradigms: Can the 'Mobilities Paradigm' Transcend Methodological Nationalism? - Kalir, Barak (Journal of ethnic and migration studies, 2013)
This article contends that an emerging 'mobilities paradigm' within the social sciences reproduces an analytical gaze that is predominantly fixated on the movement of people across national borders. This privileging of state borders and categories in many of the mobilities studies should alert us to the extent to which it brings novelty to our examination of human mobility in the world. By analysing the flow of migrant workers from rural China to Israel, this article demonstrates how new insights regarding the importance and meaning of crossing national borders can be generated by looking at mobilities through the eyes of those involved in them, allowing state categories and national borders to prefigure in the analysis to an extent and form that are relevant for migrants. The article depicts the mobility-ridden life of Tseng, who comes from a small village in Fujian province and who, after migrating internally in China several times, decides to go to Israel. Highlighting the importance of unequal capital accumulation in shaping human mobility, the article questions some taken-for-granted assumptions about the motivation and situation of those who exercise international mobility; it particularly upsets a prevalent association in migration studies between physical and socio-economic mobility.